Perbaikan Citra Dokumen Hasil Pindai Menggunakan Metode Simple, Adaptive-Gaussian, dan Otsu Binarization Thresholding - Dessy Tri Anggraeni (Universitas Bandar Lampung (UBL), 2021)
The use of digital images from scanned documents is commonly used both for data backup and for further processing. However, often the digital image obtained is not optimum due to various factors like noise. The method to improve the quality of digital images is to filter images using the Thresholding method. This study compares three Thresholding methods, which are Simple Thresholding, Adaptive-Gaussian Thresholding, and Otsu Binarization. All three methods have advantages and disadvantages. However, using the MSE and PSNR assessment parameters, the Simple Thresholding method shows better quality with an MSE value of 5,196.76, followed by Otsu Binarization with a value of 5,934.10, and Adaptive-Gaussian Thresholding with a value of 9,025.29. Meanwhile, by using PSNR, the value for Simple Thresholding is 13.37, followed by Otsu Binarization with a value of 12.47, and Adaptive-Gaussian Thresholding with a value of 10.31.